Rapid 3D navigator-triggered MR cholangiopancreatography with SPACE sequence at 3T: only one-third acquisition time of conventional 3D SPACE navigator-triggered MRCP. - Sun, Bin; Chen, Zhiyong; Duan, Qing; Xue, Yunjing; Zheng, Enshuang; He, Yingying; Lin, Lin; Li, Guijin; Zhang, Zhongshuai (Abdominal Radiology, 2020)
Purpose: The purpose of this study was to compare the proposed rapid NT-MRCP protocol and the conventional NT-MRCP protocol with respect to image quality as well as the acquisition time. Materials and methods: Between January 2019 and May 2019, a total number of 67 consecutive patients with suspected pancreaticobiliary diseases were included in this prospective study and underwent 3D rapid MRCP and 3D conventional MRCP sequences. Both acquisition protocols were set from the same navigator-triggered 3D SPACE sequence. The acquisition time was recorded. Two blinded radiologists performed qualitative analyses with respect to overall image quality, motion artifacts, and CBD visibility using a four-point scale. Quantitative evaluation included the contrast, signal-noise ratio (SNR), and contrast-noise ratio (CNR) between the common bile duct (CBD) and periductal tissues. A paired t test was used to assess differences in the qualitative and quantitative evaluations between the two acquisition methods. Results: All MRCP studies were completed successfully. The mean acquisition time of rapid NT-MRCP (96.64 ± 30.55 s) was significantly lower than that of the conventional NT–MRCP (271.42 ± 61.63 s; p < 0.001).The contrast ratio, SNR, and CNR of the CBD were significantly higher for conventional NT-MRCP than with rapid NT-MRCP images (0.95 ± 0.02 vs. 0.93 ± 0.03, p < 0.001; 10.36 ± 4.63 vs. 8.90 ± 4.71, p = 0.011; 14.01 ± 6.02 vs. 12.22 ± 6.36, p = 0.020, respectively). The rapid MRCP depicted the overall image quality, artifacts, CBD visibility, right and left hepatic duct, segment 2 branch, main pancreatic duct, and cystic duct significantly better compared with conventional MRCP (p < 0.05). There were no statistically significant differences between the two methods regarding visibility of anterior, posterior, and segment 3 branches (p > 0.05). Conclusions: In conclusion, the proposed rapid MRCP protocol yielded significantly higher overall image quality and better visualization of the pancreaticobiliary tree with a significantly reduced imaging time without deterioration of image quality compared with the conventional MRCP at 3T.